Impact of Age of Packed RBC Transfusion on Oxygenation in Patients Receiving Extracorporeal Membrane Oxygenation. Issue 9 (September 2019) - Datta, Sumit; Chang, Shelley; Jackson, Nicholas J.; Ziman, Alyssa; Federman, Myke
Abstract : Objective: To determine the effect of age of packed RBCs on tissue oxygenation in children receiving extracorporeal membrane oxygenation support. Design: A retrospective study was done between March 2013 and August 2015. The following biomarkers were examined 6 hours before and 6 hours after the conclusion of a transfusion: serum and circuit hematocrits, serum and circuit venous saturations, serum lactate levels (mg/dL), and cerebral saturation via near-infrared spectroscopy. Biomarkers were examined with respect to time relative to transfusion using four discrete categories (< 3, –3 to 0, 0–3, and > 3 hr). The association between age of blood transfusion and change in biomarkers was accessed analyzing time relative to transfusion as described above. In addition, the age of blood transfusion was analyzed similarly, using four discrete categories (0–7, 7–14, 14–21, and > 21 d). Setting: Twenty-four bed mixed pediatric medical and cardiac ICU at a tertiary care center. Subjects: Zero- to 18-year-old patients of required extracorporeal membrane oxygenation support. Interventions: None. Measurements and Main Results: Circuit venous saturation demonstrated an increase of 2.5% ( p < 0.001) in first 3 hours posttransfusion. This was followed by a 1.4% decrease after the initial 3 hours posttransfusion. Serum venous saturation showed no statistically significant change with relation to transfusions. Neither lactate levels nor near-infrared spectroscopy demonstrated any observed statistical change with relation to transfusion. With regards to the relationship between the age of RBC transfusion and tissue oxygenation biomarkers, none of the biomarkers exhibited a consistent interaction. Conclusions: Our study demonstrates that the age of packed RBC transfusion does not affect the degree tissue oxygenation in children receiving extracorporeal membrane oxygenation support, as measured by mixed venous oxygen saturation, lactate, and near-infrared spectroscopy. In addition, packed RBC transfusion, in general, did not produce any meaningful change in these markers of tissue oxygenation. Abstract : Supplemental Digital Content is available in the text.